2012
DOI: 10.1590/s0004-28032012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of nutritional risk factors using anthropometric indicators in hospitalized surgery patients

Abstract: -Context -The investigation of risk factors associated with nutritional status could contribute for better knowledge of the malnutrition. Objective -To investigate the incidence of malnutrition and its possible association with many parameters that assess nutritional status and to identify the associated risk factors. Methods -The nutritional status was assessed in 235 hospitalized patients. Malnutrition was defined as present when the patient presented at least two anthropometric criteria below the normal ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 34 publications
(46 reference statements)
1
25
0
2
Order By: Relevance
“…In the present study, it was found that 95.5% of malnourished patients developed wound healing complications and also 2 times more likely to have wound healing complications and require a significantly longer stay than well-nourished patients (7 ± 2 versus4 ± 1 days). This finding is supported by different literatures [ 6 , 14 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, it was found that 95.5% of malnourished patients developed wound healing complications and also 2 times more likely to have wound healing complications and require a significantly longer stay than well-nourished patients (7 ± 2 versus4 ± 1 days). This finding is supported by different literatures [ 6 , 14 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Aynı zamanda malnütrisyon yara iyileşmesinde gecikme ve bozulma, bağışıklık sisteminde baskılanma, kognitif fonksiyonlarda gerileme ve genel olarak fonksiyonel kapasitelerde azalma gibi önemli klinik durumların meydana gelmesinde önemli bir faktördür (1). Hastaneye yatan hastalarda malnütrisyon oranları hastane tipine, hastanenin bulunduğu bölgeye ve araştırmanın yapıldığı popülasyona bağlı olarak değişmekle birlikte %15 ile % 60 arasında değişmektedir (5)(6)(7). Malnütrisyonlu hastalarda malnütrisyonu olmayan hastalara göre daha yüksek mortalite ve morbidite oranı, daha uzun hastanede kalış süresi, daha fazla ilaç kullanımı olduğu belirtilmiştir (8).…”
Section: Introductionunclassified
“…Of the 16 studies included in the review, 13 were cross-sectional studies, where malnutrition was measured at one time point, and of these, 12 were prospective [23][24][25][26][27][28][29][30][31][32][33][34] and one was retrospective. 35 Two collected cross-sectional nutritional data across two sites 36 and preoperatively and postoperatively.…”
Section: Designmentioning
confidence: 99%
“…28 The mean number of patients per study was 252, (range 25-928). Eight studies included patients undergoing surgery for cancer, [26][27][28]30,31,[33][34][35] four were for gastrointestinal surgery, 24,25,32,36 three were for general surgery 23,37,38 and one was for emergency laparotomy 29 (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%